International journal for educational integrity : IJEI - Asia Pacific Forum on Educational Integrity; University of South Australia ([University of South Australia], 2005)
"The IJEI ... challenges readers to consider the changing nature of education in a globalised environment, and the impact that conceptions of educational integrity have on issues of pedagogy, academic standards, intercultural understanding and equity. Articles of interest to the IJEI readership may include but are not limited to the following areas as they relate to educational integrity: plagiarism, cheating, academic integrity, honour codes, teaching and learning, university governance and student motivation"--Focus and scope (publisher's Web site, viewed Jan. 27, 2006).
Keywords: Education, Higher : Moral and ethical aspects : Periodicals; College students : Conduct of life : Periodicals; College teachers : Professional ethics : Periodicals; Integrity : Study and teaching (Higher) : Periodicals; Honor system (Higher education) : Periodicals; Cheating (Education) : Periodicals; Plagiarism : Periodicals; Cheating (Education); College students : Conduct of life; College teachers : Professional ethics; Education, Higher : Moral and ethical aspects; Honor system (Higher education); Plagiarism